2022
DOI: 10.1007/s40675-022-00234-5
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Children with Autism Spectrum Disorder: A Narrative Review and Systematic Update

Abstract: Purpose of Review Sleep problems are a common comorbidity for children with autism spectrum disorder (ASD), and research in this area has a relatively long history. Within this review, we first outline historic patterns in the field of sleep and ASD. Second, we conducted a systematic update and coded these studies based on their alignment with historic patterns. Research on ASD and sleep over the past two decades has primarily focused on four principal areas: (1) documenting the prevalence and typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…First, many studies are based on subjective data, gathered from parental questionnaires, rather than objective measures of sleep 27 . Second, the number of children evaluated in any given study using actimetry or other objective measures has been small, with frequently less than one hundred per study 27,28 . Third, because of conflicting data, it is unclear whether children with ASD and ID differ from those with ASD without ID with respect to the degree of sleep disturbance 7,2932 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, many studies are based on subjective data, gathered from parental questionnaires, rather than objective measures of sleep 27 . Second, the number of children evaluated in any given study using actimetry or other objective measures has been small, with frequently less than one hundred per study 27,28 . Third, because of conflicting data, it is unclear whether children with ASD and ID differ from those with ASD without ID with respect to the degree of sleep disturbance 7,2932 .…”
Section: Introductionmentioning
confidence: 99%
“…The data currently available on sleep in children with ASD are restricted by several experimental limitations that also complicate interpretation. First, many studies are based on subjective data, gathered from parental questionnaires, rather than objective measures of sleep 27 . Second, the number of children evaluated in any given study using actimetry or other objective measures has been small, with frequently less than one hundred per study 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…The resulting impact reverberates across a comprehensive spectrum of domains, encompassing the intricate threads of communication, the fabric of learning, the dance of social behavior, and the tapestry of motor skills. While ASD maintains its distinct identity with unique attributes, acknowledging the latent potential for multiple neurodevelopmental disorders to converge within the presentation of children remains of paramount significance [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…As ASD involves differences in brain maturation and neuronal differentiation, these changes should be observable early in development. Indeed, spindles are well known to evolve with age (42) (39) and have been proposed as markers of brain maturation (43) (44) (45) (46).…”
Section: Introductionmentioning
confidence: 99%
“…As ASD involves characteristic differences in brain maturation, these changes should be observable early in development. Indeed, spindles are well known to evolve with age (42) (39) and have been proposed as markers of brain maturation (43) (44) (45) (46). Page et al performed a daytime nap study of NREM sleep in children with ASD compared to typically-developing (TD) controls aged 13-30 months and found specific changes in theta, fast sigma and beta oscillations (18) In this present study we utilized the dataset reported in Farmer et al, enlarged following their publication (15% increase in participants), to further investigate NREM sleep neurophysiology in children with ASD, extending the list of the investigated spindle characteristics and including analyses of SO and coupling between spindles and SOs which were not performed in this sample before.…”
Section: Introductionmentioning
confidence: 99%